Implementation of an OLT (Optical Line Terminal) Based FTTH (Fiber To The Home) Network in Mandala Jaya Village to Optimize internet Connectivity - Hilmy Harsyadianto Fadhilah; Rini Astuti; Willy Prihartono; Ryan Hamonangan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research aims to optimize internet connectivity in Mandala Jaya Village through the application of Fiber To The Home (FTTH) technology based on Optical Line Terminal (OLT). This village previously relied on conventional cable network infrastructure which was prone to weather and physical disturbances, thereby reducing the quality of internet services. With research methods based on problem identification, architectural design, implementation, measurement and analysis of results, this research succeeded in evaluating network performance using an Optical Power Meter (OPM) and other testing tools. The results show that the OLT-based FTTH network provides higher speeds, better connection stability, and operational cost efficiency compared to conventional media converters. The optimal attenuation value is measured in the range of -19 dBm to -24 dBm, which is in accordance with international standards. These findings support switching to network infrastructure in similar villages as a more reliable connectivity solution.